Synthesis and performance of ultrafiltration membranes incorporated with different oxide nanomaterials: experiments and modeling - Nawaf Bin Darwish; Abdulrahman AlAlawi; Hamad AlRomaih; Nasser Alotaibi; Musaad AlEid (Journal of Water Reuse and Desalination, 2023)
In membrane filtration technology, membrane fouling is the primary obstacle to optimizing efficiency and results in a short membrane lifetime and high operating costs. By incorporating nanomaterials into the membrane synthesis process, a mixed-matrix membrane with significantly enhanced characteristics and performance may be obtained. Graphene oxide (GO), aluminum oxide (Al2O3), tin oxide (SnO2), and titanium oxide (TiO2) were incorporated into a polyethersulfone (PESU) membrane. The water permeability of the modified membranes showed improvements when compared with the pure membrane. It increased from 65 L/m2 h bar for the pristine membrane (PES-1) to 143.6, 83.68, 92.12, 75.43 L/m2 h bar for Al2O3 (PES-2), TiO2 (PES-3), SnO2 (PES-4), and GO (PES-5) membranes, respectively. It was discovered that the membrane's surface hydrophilicity was significantly and directly affected by the incorporation of nanoparticles. Fouling parameters include Rr (Reversible fouling ratio), Rir (irreversible fouling ratio), Rt (total fouling ratio), and Frr (flux recovery ratio) and were measured to determine the membrane's fouling tendency. The results showed that the membrane's propensity for fouling could be reduced when nanoparticles were incorporated into it. The experimental results are best explained by the cake layer and both standard and intermediate blocking mechanism models, as determined by the traditional single fouling models. HIGHLIGHTS Ultrafiltration membranes were incorporated with different nanomaterials.; Different fouling models were fitted to the experimental data.; The fouling parameters were measured to determine the membrane fouling tendency.; Water flux improved as a result of pore formation and hydrophilicity enhancement.;